Forum 2: Suicide During COVID-19 - Md Zin, Ahmad Rostam; Mohamad, Farhah Syakirah; Abdul Khaiyom, Jamilah Hanum; Norzan, Mohd Hafiz (International Journal of Human and Health Sciences (IJHHS), 2022)
The COVID-19 pandemic has affected us in many ways. To protect us from COVID-19 infection spread, we had to follow new rules or “SOP” that resulted in isolation, change of work or studying environment, loss of income and emotional disturbance. Many had to adapt to the new condition, but some found it overwhelming. The Malaysian police department reported 638 cases of suicide until July 2021 which is equivalent to a nearly 60% increase compared to last year. This is an alarming report which requires action to be taken at many levels. Awareness about the importance of mental health and understanding mental illnesses are slowly improving but the stigma is still present which deters people from seeking appropriate help. Healthcare professionals are also experiencing burnout due to the current pandemic and are also vulnerable to emotional disturbance. Hence, it is time to discuss this topic with experts from diverse backgrounds to understand issues related to suicide, especially during this pandemic. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S13